Changes in Concentration in Manufacturing Industries in the United States, 1954-1966: Trends and Relationships to the Levels of 1954 Concentration - Bain, Joe S. (The Review of Economics and Statistics, 1970)
Joe S. Bain, Changes in Concentration in Manufacturing Industries in the United States, 1954-1966: Trends and Relationships to the Levels of 1954 Concentration, The Review of Economics and Statistics, Vol. 52, No. 4 (Nov., 1970), pp. 411-416